2006
DOI: 10.1177/039463200601900311
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effect of an Immunostimulating Bacterial Lysate on Human B Lymphocytes

Abstract: The aim of the present study is to investigate in humans the mechanism by which the oral vaccine Polyvalent Mechanical Bacterial Lysate (PMBL) can rapidly mobilize specific immune response and evaluate the efficacy of its immunostimulating activity in preventing recurrent infections of the upper respiratory tract (URTIs) in a group of patients with a medical history of URTI recurrence. Patients received, by sublingual route, PBML, an immunostimulating lysate obtained by mechanical lysis of the most common bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
1
24
1
1
Order By: Relevance
“…Кроме того, пероральное введение ПМБЛ привело к значительному повышению индукции синтеза цитоки-нов (ИЛ-2, ИЛ-4, ИЛ-10, интер ферона-γ) в иммунокомпе-тентных клетках, которые инициируют и регулируют иммунный ответ [5]. Было также доказано, что перораль-ное применение ПБЛ значительно стимулировало про-дукцию CD4+-и CD8+-Т-клеток, специфических подтипов В-клеток, так называемых В-лимфо цитов памяти (CD24+-/CD27+-клетки), ИЛ-2-рецептор экспрессирую-щих лимфоцитов (CD25+-клетки) [5][6][7][8]. Недав ние иссле-дования на лабораторных животных предо ста вили доказательства, что пероральное введение ПБЛ приво-дит к уменьшению аллергического воспаления дыха-тельных путей [9].…”
Section: инфекции в оториноларингологииunclassified
“…Кроме того, пероральное введение ПМБЛ привело к значительному повышению индукции синтеза цитоки-нов (ИЛ-2, ИЛ-4, ИЛ-10, интер ферона-γ) в иммунокомпе-тентных клетках, которые инициируют и регулируют иммунный ответ [5]. Было также доказано, что перораль-ное применение ПБЛ значительно стимулировало про-дукцию CD4+-и CD8+-Т-клеток, специфических подтипов В-клеток, так называемых В-лимфо цитов памяти (CD24+-/CD27+-клетки), ИЛ-2-рецептор экспрессирую-щих лимфоцитов (CD25+-клетки) [5][6][7][8]. Недав ние иссле-дования на лабораторных животных предо ста вили доказательства, что пероральное введение ПБЛ приво-дит к уменьшению аллергического воспаления дыха-тельных путей [9].…”
Section: инфекции в оториноларингологииunclassified
“…However, positive outcomes have been observed using bacterial lysates to promote immunostimulation as a method to prevent infection [78], or bacterial interference to suppress pathogenic bacteria in an attempt to reduce antibiotic use [79].…”
Section: Implementing An Antibiotic Stewardship Programmementioning
confidence: 99%
“…15 Furthermore, another study 16 demonstrated that this PMBL had several immunologic effects consisting in: The same study group analyzed the effect, in vivo, of the PMBL (orally administrated) in preventing recurrent infec-tions of the upper respiratory tract (URTIs) in a group of patients with a medical history of URTI recurrence. 17 Clinical results were correlated to the levels of IgM memory B cells and the expression of the activation marker CD25 in peripheral blood lymphocytes using the flow cytometric method, before and at 1 and 3 months after the treatment. PMBL have shown to exert a therapeutic and preventing effect in acute and recurrent infections of the upper airways, which is significantly correlated with the activation and enhancement of both IgM memory B lymphocytes (CD24 ϩ /CD27 ϩ cells) and IL-2 receptor-expressing lymphocytes (CD25 ϩ cells) involved either in humoral or cellular immunity.…”
Section: Molecular and Immunologic Mechanisms Of Actionmentioning
confidence: 99%